PSXIV-33 Impacts of Bos indicus vs. Bos taurus genetics and nutrient energy restriction during early gestation on offspring performance and feed efficiency. (7th December 2018) - Fontes, P; Oosthuizen, N; Ciriaco, F; Henry, D; Sanford, C; Canal, L; Mercadante, V; Ealy, A; Johnson, S; DiLorenzo, N; Lamb, G
Abstract: The objective of this experiment was to evaluate the effects of Bos indicus and Bos taurus genetics, as well as dietary energy restriction during early gestation, on postnatal performance of the offspring. Reciprocal embryo transfers were conducted in a completely randomized design using a 2 × 2×2 factorial arrangement of treatments. Recipient cows were housed in the University of Florida Feed Efficiency Facility (FEF), equipped with a GrowSafe feed intake monitoring system, and were randomly assigned to 1) a diet to meet maintenance requirements (MAINT), or 2) a diet that restricted energy intake to 70% of maintenance requirements (RESTR). Angus (AN) and Brangus (BN) female embryos were then randomly transferred on d 7 to either AN or BN recipients fed the respective diets for 27 d. Recipients remained on the dietary scheme until d 91 of gestation. Cows were then commingled and fed a common diet that met their energy requirements until calving. Offspring were placed in the FEF after weaning and were submitted in a 70-d feed efficiency test. No significant effects were observed on gestation length, calf birth weight, and weaning weights ( P> 0.10). There was a tendency ( P= 0.09) for greater dry matter intake in heifers from BN recipients compared to heifers from AN recipients. However, heifers from AN recipients tended to have greater average daily gain than those from BN recipients ( P= 0.08). In addition, heifers from BN recipients tended to have greater residual feed intake ( P= 0.07) and had greater gain to feed ratio ( P= 0.03) when compared to heifers from AN recipients. There were no significant interactions, nor main effects of diet or embryo breed on any evaluated response variables ( P> 0.10). In conclusion, energy restriction during early gestation and embryo breed did not alter offspring performance; however, recipient breed influenced offspring postnatal feed efficiency.